Critical Discourse Analysis: Revealing The Masculinity On Alpha Rules By Deddy Corbuzier - Feri Cahya Nugraha; Marshall Verli (Jurnal Pendidikan Indonesia, 2022)
Advertisement is one of crucial movements to influence the product social engagement. There are also some factors which influencing the success of advertisement, one of the factors is the role model. As we know, the role model of the advertisement may bring a huge impact to the advertisement, for example the Alpha Rules by Deddy Corbuzier. The Advertisement of Alpha Rules was quite crucial and bring a lot message to the readers, especially for men. Therefore, this paper mainly discusses the critical discourse on the Alpha Rules by Deddy Corbuzier. The writers aim to reveal some topics that can be discussed related to the object which is being investigated. Looking at the product advertisement, the writers aim to analyze several topics, for instance, the use of language, logo, and slogan. Furthermore, the writers also aim to analyze the product's masculinity issues and the effect of Deddy Corbuzier's popularity on his product. Therefore, by considering several topics which begin the discussion on this paper, the writers intend to apply the Fairclough approach to analyze the research problems.